Kritik Syeikh Abdul Halim Mahmud terhadap Sekte-Sekte Syiah: Antara Sejarah, Akidah, dan Tafsir - Nuraini; Halimatussadiyah; Kusnadi; Pathur Rahman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the critical perspective of Shaykh Abdul Halim Mahmud, the Grand Shaykh of Al-Azhar, on various Shia sects, particularly in terms of theology and interpretive methodology. He differentiates between extremist and moderate Shia groups and rejects the generalization of declaring all Shia as disbelievers. Using a qualitative approach and literature study of his major work, Al-Tafkīr al-Falsafī fī al-Islām, Mahmud highlights Shia exegesis that relies heavily on infallible Imams and esoteric interpretations, which he considers deviations from the outward meaning of the Qur'an. He classifies Shia sects from the extreme Ghulat, Imamiyah and Ismailiyah, to the more moderate Zaydiyyah, which he views as closer to Ahlus Sunnah. Mahmud presents his views through a scholarly and non-provocative approach, contributing to a broader understanding of intra-Muslim pluralism. His critique holds not only academic value but also strategic significance in mitigating sectarian conflict and promoting constructive inter-sectarian dialogue..